Two-phase Flow Model and Productivity Evaluation of Gas and Water for Dual-Medium Carbonate Gas Reservoirs - Kang, Lixia; Guo, Wei; Zhang, Xiaowei; Liu, Yuyang; Gao, Jinliang; Shao, Zhaoyuan; Li, Min; Sun, Yue (Frontiers in Earth Science, 2022)
Fluid flow in the dual-medium carbonate gas reservoir is greatly different from that in the conventional gas reservoir. It is characterized by stress sensitivity and non-Darcy flow effect. The unsteady seepage in the dual-medium gas reservoir is affected by the stress sensitivity and non-Darcy flow. To accurately describe this, a two-phase seepage model of gas and water that considers both the stress sensitivity and non-Darcy flow is built based on the fundamental seepage theory, after fully investigating the reservoir space and fluid flow characteristics of carbonate gas reservoirs. Then, the perturbation theory is introduced, and the model is solved in the Laplace space, after which the obtained Laplace space analytical solution is converted into the real-space solution. Finally, the productivity evaluation model for the dual-medium gas reservoir with the gas-water two-phase flow is built, based on the flowing material balance method and Newton iteration. The presented productivity evaluation model is applied to analyze the effects of stress sensitivity and non-Darcy flow on the two-phase seepage model of gas and water for the dual-medium gas reservoir and the reservoir productivity. A higher stress sensitivity coefficient is demonstrated to indicate higher stress sensitivity and accelerated production decline of the reservoir, while a lower non-Darcy flow effect coefficient represents a stronger non-Darcy effect and boosted drop of initial production of the reservoir. Hence, it is not reasonable to neglect the effects of stress sensitivity and non-Darcy flow during the evaluation of the productivity of a dual-medium carbonate gas reservoir. The model presented in this research provides important references for improving the recovery performance of dual-medium gas reservoirs.